2016
DOI: 10.1002/gea.21565
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of a Shallow Water Wave‐Dominated Shipwreck Site: Fougueux (1805), Gulf of Cadiz

Abstract: The evolution of the shallow water wave-dominated Fougueux wreck site in the Gulf of Cadiz was investigated through repeat bathymetric surveys, wave-and current-velocity field measurements, and numerical modeling. This multidisciplinary approach was used to understand the relationships between scouring, morphodynamic change, and hydrodynamic forcing. Field experiments and numerical models indicate that wave processes dominate site evolution. Numerical model outputs indicate current velocity, bed shear stress, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…This necessitates use of non-destructive imaging techniques, which can be used to represent the digitally-preserved record of the wreck and create detailed visualizations for the non-diving public, enhancing awareness of the underwater cultural heritage (Calder et al 2007;Dean et al 2007;Eriksson and Rönnby 2012). Imaging of the wreck and surrounding seabed also allows documentation of the wreck structure, and time-lapse surveys allow physical processes acting on sites to be assessed providing insights into the rate and pattern of degradation (Astley et al 2014;Fernandez-Montblanc et al 2016;Manders 2009;Mertes et al 2017;Quinn & Boland 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This necessitates use of non-destructive imaging techniques, which can be used to represent the digitally-preserved record of the wreck and create detailed visualizations for the non-diving public, enhancing awareness of the underwater cultural heritage (Calder et al 2007;Dean et al 2007;Eriksson and Rönnby 2012). Imaging of the wreck and surrounding seabed also allows documentation of the wreck structure, and time-lapse surveys allow physical processes acting on sites to be assessed providing insights into the rate and pattern of degradation (Astley et al 2014;Fernandez-Montblanc et al 2016;Manders 2009;Mertes et al 2017;Quinn & Boland 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Seasonal changes are observed, showing accretion during a low waveenergy period (LEP) from May to September and net erosion around the hull structure during a high-energy period (HEP) from November to April (Fernández-Montblanc et al, 2016). At the deepest point at the centre of the wreck site (x~=192) minor seasonal variations were found (Figure 1a and Figure 1c).…”
Section: Study Sitementioning
confidence: 98%
“…Previous investigations at the wreck site (Fernández-Montblanc et al, 2016), based on time-lapse bathymetric surveys and conventional hydrodynamic modelling, concluded that sediment is alternatively deposited and eroded at the Fougueux site in response to seasonal wave climate variation. Thus the morphological changes observed in HEP and LEP are intrinsically linked to the seasonal wave climate variation in an inter-annual interactive cycle.…”
Section: Bed Shear Stressmentioning
confidence: 99%
“…This perturbation in the system can result in either a new equilibrium state or maintenance of the current one, depending on the system's capacity to absorb external forces (Astley, 2016; Quinn, 2006; Quinn & Boland, 2010). The dynamics of equilibrium varies across wreck sites, with some subject to disruptions by storms (Fernández‐Montblanc et al, 2016, 2018; McNinch et al, 2006), varying tidal currents (Astley, 2016; Quinn & Smyth, 2018), or anthropogenic impacts (Brennan et al, 2013; Gibbs, 2006), whereas others are nearly static, located in more stable physical environments (Eriksson & Rönnby, 2012). What is common is that all wreck sites are characterized by a negative disequilibrium trend, as they undergo a gradual degradation due to chemical (i.e., corrosion) and biological (e.g., wood‐boring organisms) formation processes (Foecke et al, 2010; Gregory, 2020; Pournou, 2017; Taormina et al, 2020).…”
Section: Introductionmentioning
confidence: 99%